Impact of tax discrimination, tax knowledge, and sanctions on tax Evasion perception - Putri Indah Wahyuni; Najela Tsaqila Fatma Meimun; Amri Amrulloh (Inovasi Analisis Data, 2024)
Purpose – The purpose of this study is to analyze effect of tax discrimination, tax knowledge, tax sanctions and taxpayer ethics on perception of tax evasion. It seeks to discover is how these factors affect the behavior and compliance of Indonesian taxpayers.Design/methodology/approach – Tax discrimination, tax knowledge, tax sanctions, taxpayer ethics, and tax evasion perception were measured using a structured questionnaire with a five-point Likert scale. SPSS was used to analyse the data, employing multiple regression analysis, with the measurement held to validity and reliability tests.Findings – The results demonstrates that tax discrimination and weak taxpayer ethics increase tax evasion perception while strong tax knowledge and high tax sanctions serve as deterrent factors. The results underscore the role of a fair and transparent taxation system in mitigating tax evasion tendencies.Originality/value – This study adds to the tax compliance literature by combining a behavioral and regulatory perspective of tax compliance. For this reason, it delivers empirical insight about the influence of perceived fairness and ethical issues upon tax compliance attitudes in emerging economies.Research Implications – The research holds great significance for tax authorities in formulating more equitable tax legislation with improved enforcement mechanisms. Providing an understanding of taxes, as well as strict but fair penalties, can improve taxpayer compliance and minimize risk of evasion